Crossing Boundaries to Advance Nursing Research Education. Issue 3 (May 2019) - Cronin, Sherill Nones; Berger, Jill; Nelson, Debbie; Romp, Celeste R.; Stikes, Reetta; Wishnia, Gracie
Abstract : Nursing professional development specialists may find it challenging time and cost-wise to meet the educational needs of nurses in the areas of research and evidence-based practice amidst competing education priorities. Furthermore, it may be difficult to find presenters with the necessary knowledge and expertise to do so. Collaboration among local hospitals to provide a high-quality research education program can advance scholarly work within the community and can help each organization meet selected Magnet® requirements in an economical way.